(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article explores the fascinating origins and linguistic roots of the names of various mythical creatures and figures from diverse cultures around the world. By delving into the etymology, the study reveals how these names reflect the cultural perceptions, attributes, and historical contexts of the entities they describe. The article begins with an analysis of well-known mythical creatures such as dragons, phoenixes, and werewolves. For instance, the term "dragon" is traced back to the Greek word "dragōn," meaning "serpent" or "giant sea fish," highlighting the creature’s feared and awe-inspiring nature across cultures. Similarly, the phoenix, a symbol of rebirth and immortality, is examined through its Greek origins, where "phoenix" referred to a mythical bird associated with the sun.